ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL TEORI KINETIK GAS SMA NEGERI 1 KENDAWANGAN - Permatasari, Melani; Maria, Haratua Tiur; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research is to analyze the student’s mistake make in answering questions about the kinetic theory os gas and finding the cause of the mistake. The method of this research was descriptive method. Essays dan interviews were the tools of data collection which were given to upper, medium,and lower level students. Sample of this research was 23 students 11th grade of SMAN 1 Kendawangan. The result showed that the kind of mistakes were unit mistake (59,13%), formula mistake (19,56%), count mistake (26,14%). Students often make mistake in deciding the unit because they were not careful, in rush and they cooperate as well. On the other hand, students made mistake in counting because they were not careful and in rush. The hope of this research was teacher can help the students in solving the questions correctly Keywords : analysis mistake profile, complete question, presentation mistake,reason mistake